Alam Cetak / Atasya Syuhada Mohamad, Mohd Haziq Asfa Md Shapari … [et al.] - MOHAMAD, ATASYA SYUHADA; MD SHAPARI, MOHD HAZIQ ASFA; MOHD, NURUL HIDAYATUL AMYRA; UNGKU IBRAHIM, UNGKU AINAA UL-MARDHIAH (2018)
The Alam Cetak Enterprise is a printing business that started by Mr. Mohamed Azrul Noor Azizul Rahim, located on the second floor of double-storey shop in Bandar Puncak Alam, Selangor. Along with Mr. Mohamed Azrul as the director, Mr. Muhamad Danial Bin Ariffin as the manager and followed by three staff in which two of them assign for printing while one of them assigns in graphic and layout. This business started the first operation on March, 2016. Their operational time from 7am to 3pm and from 9pm to 2am. Started with several small printing and photocopying devices such as the Ricoh-branded machine, this business has expanded in their operation by adding larger printing devices such as plot printing that specialized in printing and plotting paper plan such as architectural plan. Moreover, this company also served other services such as laminating, binding and sticker-customizing.